1988
DOI: 10.1111/j.1524-4725.1988.tb03503.x
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Facial Scars by Programmed Dermabrasion

Abstract: Revisions of scars, characteristically deferred for 6 to 12 months after wounds have healed, are performed to improve function and appearance. However, none of the techniques that has evolved to modify cicatrical deformities has afforded total, permanent effacement of scars already present. Evidence is presented here that dermabrasion of both surgical and accidental scars of the face, done 4 to 8 weeks after the primary wound, usually eliminates visible residual cicatrization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(29 citation statements)
references
References 3 publications
0
29
0
Order By: Relevance
“…Wire and diamond fraise dermabrasion, surgical sand paper, chemical peels, and lasers have all been used to resurface scars [5]. Although several earlier authors recommended resurfacing scars 3±9 months postoperatively [6], in 1988 Yarborough [7] demonstrated that scars dermabraded 4±8 weeks postoperatively showed more improvement than those dermabraded at longer intervals from the primary wound. In a split scar study, Katz and Oca [8] found a greater number of scars responded to dermabrasion at 8 weeks than at 4±6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Wire and diamond fraise dermabrasion, surgical sand paper, chemical peels, and lasers have all been used to resurface scars [5]. Although several earlier authors recommended resurfacing scars 3±9 months postoperatively [6], in 1988 Yarborough [7] demonstrated that scars dermabraded 4±8 weeks postoperatively showed more improvement than those dermabraded at longer intervals from the primary wound. In a split scar study, Katz and Oca [8] found a greater number of scars responded to dermabrasion at 8 weeks than at 4±6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Yarborough 2 proposed that dermabrasion restructures and layers collagen parallel to the lines of tension to smooth contour irregularities and eliminates the epidermal component by upward and horizontal migration of epithelial cells from viable adnexal structures. Nelson et al 22 demonstrated an increase in collagen type I synthesis after superficial dermabrasion for photoaged skin.…”
Section: Methodsmentioning
confidence: 99%
“…Many authors have reported excellent results achieved with this device. [1][2][3][4][5][6] The disadvantages of the powered tool include aerosolizing of infectious particles; blood splatter; the need for protective clothing; risk of lip, eyelids, hair, or gauze being caught in the instrument; and the added cost of the power instrument. Several authors have reported manual use of abrading devices for dermabrasion, including wire brush, DF, sandpaper, Bovie scratch pads, abrasive cloth, and drywall or plaster sanding screen (SS).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the skin receives its vascular supply via the arborized papillary plexus and the deep vascular plexus at the dermal-subcutaneous tissue junction, pinpoint bleeding serves as an important landmark to indicate the depth of the papillary dermis. 9 The healing process is initiated by coagulation of the wound edge and crust formation during the first 24 hours. Locally, activation of coagulation cascade triggers complex signaling pathways including the release of chemotactic and growth factors (i.e., transforming growth factor-beta [TGF-β], fibroblast growth factor [FGF], epidermal growth factor [EGF], transforming growth factor-alpha [TGF-α], and platelet-derived growth factor [PDGF]) involved in endothelial cell and fibroblast proliferation.…”
mentioning
confidence: 99%